Residual Deformity Is the Most Common Reason for Revision Hip Arthroscopy: A Three-dimensional CT Study - Ross, James R. (Clin Orthop Relat Res, 2014)
BACKGROUND: Previous studies have reported residual deformity to be the most common reason for revision hip arthroscopy. An awareness of the most frequent locations of the residual deformities may be critical to minimize these failures. QUESTIONS/PURPOSES: The purposes of this study were to (1) define the three-dimensional (3-D) morphology of hips with residual symptoms before revision femoroacetabular impingement (FAI) surgery; (2) determine the limitation in range of motion (ROM) in these patients using dynamic, computer-assisted, 3-D analysis; and (3) compare these measures with a cohort of patients who underwent successful arthroscopic surgery for FAI by a high-volume hip arthroscopist. METHODS: Between 2008 and 2013, one senior surgeon (BTK) performed revision arthroscopic FAI procedures on patients with residual FAI deformity and symptoms after prior unsuccessful arthroscopic surgery; all of these 47 patients (50 hips) had preoperative CT scans. Mean patient age was 29 ± 9 years (range, 16–52 years). Three-dimensional models of the hips were created to allow measurements of femoral and acetabular morphology and ROM to bony impingement using a validated, computer-based dynamic imaging software. During the same time period, 65 patients with successful primary arthroscopic treatment of FAI by the same surgeon underwent preoperative CT scans for the symptomatic contralateral hip; this group of 65 patients thus fortuitously provided postoperative evaluation of the originally operated hip and served as a control group. A comparison of the virtual correction with the actual correction in the primary successful FAI treatment cohort was performed. Correspondingly, a comparison of the recommended virtual correction with the correction evident at the time of presentation after failed primary surgery in the revision cohort was performed. Analysis was performed by two independent observers (JRR, OA) and a paired t-test was used for comparison of continuous variables, whereas chi-square testing was used for categorical variables with p < 0.05 defined as significant. RESULTS: Ninety percent (45 of 50) of patients undergoing revision surgery for symptomatic FAI had residual deformities; the mean maximal alpha angle in revision hips was 68° ± 16° and was most often located at 1:15, considering the acetabulum as a clockface and 1 to 5 o’clock as anterior independent of side. Twenty-six percent (13 of 50) of hips had signs of overcoverage with a lateral center-edge angle greater than or equal to 40°. Dynamic analysis revealed mean direct hip flexion of 114° ± 11° to osseous impingement. Internal rotation in 90° of hip flexion and flexion, adduction, internal rotation to osseous contact were 28° ± 12° and 20° ± 10°, respectively, which were less than those in hips that had underwent hip arthroscopy by a high-volume hip arthroscopist (all p < 0.001). CONCLUSIONS: We found marked radiographic evidence of incomplete correction of deformity in patients with residual symptoms compared with patients with successful results with residual deformity present in the large majority of patients (45 of 50 [90%]) undergoing residual FAI surgery. We recommend careful attention to full 3-D resection of impinging structures. LEVEL OF EVIDENCE: Level III, retrospective study, case series.